PENERAPAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN PROSES DAN HASIL BELAJAR KELAS III SEKOLAH DASAR - Tri Wiyoko; Nurlev Avana; Misdaleni Misdaleni (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2022)
This study began with the low student learning outcomes in class III caused by the learning process that is not optimal. This type of research is classroom action research. This class action research includes the stages of planning, implementation, observation, and reflection. The subjects of this study were students in grade III SDN No.152 / II Renah Jelmu with a total of 18 students. Data collection techniques used were tests and observation sheets. The research instruments used included the Learning Implementation Plan with the Problem Based Learning (PBL) model, test questions and observation sheets. The data analysis technique used is descriptive analysis while the research approach is quantitative. The research results obtained are as follows; (a) the teacher conducts learning interactively so that the learning process in cycle I runs well and increases in cycle II with very good criteria. (b) Students become active in the learning process, this is shown from the learning activities of students in the first cycle with good enough criteria and then increase in the second cycle with good criteria. (c) Problem Based Learning Model taught coherently will train students' understanding ability, this can be seen from the results of student learning that increased from cycle I only by 78% to 89% in cycle II with very good criteria.